53 interesting things to do in your lectures : tips and strategies for really effective lectures and presentations /: tips and strategies for really effective lectures and presentations. (2020) - Haynes, Anthony; Haynes, Karen, 1960-; Habeshaw, Sue; Gibbs, Graham; Habeshaw, Trevor
No abstract available